The Existence of the State's Role in Providing Prodeo Legal Aid to Citizens Who Are Not Able Based on Law Number 16 of 2011 - Helmy Yahya Rahma Aji; Raden Muhammad Arvy Ilyasa (Universitas Negeri Semarang, 2020)
Indonesia as a state of the law has guaranteed the constitutional rights of each of its citizens without exception as a form of protection of human rights contained in Article 1 paragraph (3) of the 1945 Constitution. Providing legal assistance to citizens who are unable as constitutional rights of every citizen and the State is obliged to protect the constitutional rights regarding obtaining guarantees, protections, and certainty of law that is fair and equal treatment before the law. Legal aid legally in Law Number 16 of 2011 is a legal service free of charge to legal aid recipients. The thing that becomes the basis for the provision of legal assistance by the State is because the State is responsible for providing legal assistance to disadvantaged citizens as a form of access to justice and equality before the law. The state has a role in terms of establishing regulations as the legal basis for implementing legal assistance for disadvantaged citizens. But in reality, in the development of legal aid, there are several problems between legal aid providers (advocates) and the State as a guarantor of the constitutional right to the realization of justice and equality before the law for every Indonesian citizen, including the poor.